Difficulties in learning English listening skills: The case of 10-grade students at Thang Long High School . M.A Thesis Linguistics: 60 14 10 - Vũ, Quỳnh Trang (University of Languages and International Studies, 2017)
This study has been conducted to investigate difficulties 10-grade students at Thang Long High School, Ha Noi face through their listening learning process with the textbook “Tieng Anh 10”. The subjects of the study are 100 10-grade students of Thang Long (...)